Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China - Wang, Dan; Yin, Zi-Wei (Zootaxa, 2016)
Following our previous contributions to the knowledge of Chinese Batraxis Reitter (Wang et al. 2016; Wang & Yin 2016), here we describe two more species from Yunnan, and provide new collecting records for two previously described species, based on the newly available material deposited in the National Museum, Prague, Czech Republic. The number of Batraxis species now reaches 63 species, 19 of them are known to occur in China.